Regulators of G protein signalling: a spotlight on emerging functions in the cardiovascular system - Wieland, Thomas; Lutz, Susanne; Chidiac, Peter (Current opinion in pharmacology, 2007)
Regulator of G protein signalling (RGS) proteins are GTPase-activating proteins for heterotrimeric G protein a subunits, and are therefore physiologically and pathophysiologically important negative regulators of G-protein-coupled receptor signalling in the cardiovascular system. Owing to the functional redundancy of many of the 20 RGS, and more than 20 RGS-like, proteins even within a single cell, animal models shedding light on the functions of individual RGS proteins are often missing. Nevertheless, RGS2 is a member of this protein family, for which specific functions in the vasculature and the heart are now emerging. Recent data show that the 519-amino acid RGS3, the only RGS protein with an additional G protein beta gamma dimer binding domain, largely alters the signalling of G(i) proteins to the monomeric GTPases Rac1 and RhoA in cardiomyocytes. In addition, an alternative approach using transgenic animals expressing RGS-resistant G protein alpha subunits now highlights the contributions of RGS proteins to distinct signalling pathways in the heart.